Effects of enzyme-treated palm kernel expeller on its nutritive value, and growth performance and carcass quality of broiler chickens - Saenphoon, Pornpan (2012)
Palm kernel expeller (PKE) contains high fiber which is mainly in the form of highly non-digestible mannan-hemicellulose. Pre-treating PKE with exogenous enzymes to hydrolyze the insoluble oligosaccharides is an option to enhance the efficiency of the utilization of this agro-industrial byproduct by monogastric animals such as the poultry. The primary objectives of this thesis were to examine the effect of enzyme treatment on the nutritive value of PKE and the effect of feeding the enzyme treated PKE on growth performance and carcass quality in broiler chickens. Three experiments were conducted to achieve the above objectives. The effect of enzyme treatment on chemical composition and production of reducing sugars in PKE was evaluated. Results showed that enzyme treatment decreased (P<0.05) hemicelluloses and cellulose contents by 35.70 and 22.14%, respectively, and increased (P<0.05) the content of reducing sugars by about 36 folds. Extract of enzyme treated PKE had significantly higher (P<0.05) mannanase and cellulase enzymes than those in the raw PKE. Effects of the enzyme treatment on apparent (AME) and true (TME) metabolizable energy of PKE in broiler chickens were estimated in experiment 2. Chickens were assigned to three experimental diets: raw PKE, enzyme treated PKE and corn (as control). The results showed that although enzyme treatment increased AME and nitrogen corrected AME (AMEn) by 4.0 and 4.4%, respectively, compared to the raw PKE, the values were not statistically different. However, enzyme treatment increased (P<0.05) TME (7.55 MJ/kg) and its nitrogen corrected value (TMEn; 6.54 MJ/kg) values by 37.6 and 33.0%, respectively, compared to the raw PKE (4.71 and 4.38 MJ/kg, respectively). In experiment 3, the effects of inclusion of enzyme treated PKE on growth performance [during grower (21 days) and finisher (41 days) stages], intestinal villus height, digesta viscosity and carcass quality in broiler chickens were investigated. Commercial broiler chickens (Cobb 500) were fed with a commercial starter diet followed by combinations of three experimental grower diets (0% raw PKE, 5% raw PKE and 5% enzyme treated PKE) and five finisher diets (0% raw PKE, 20% raw PKE, 20% enzyme treated PKE, 30% raw PKE and 30% enzyme treated PKE). Average daily gain (ADG), feed intake and feed conversion ratio (FCR) of chickens fed on different dietary treatments in the grower period were not significantly different. Although there was no difference in feed intake (P>0.05) among treatment groups in the finisher period, ADG of chickens in the control (PKE-free diet) was significantly higher (P<0.05) than in all treatment groups fed either 20 or 30% PKE and irrespective of with or without enzyme treatment. However, ADG of birds fed with 20% PKE was higher than those fed with 30% PKE. The FCR of chickens in the control was the lowest (2.20) but not significantly different from those fed 20% PKE diets while birds in the 30% PKE diets recorded higher (P>0.05) FCR. The above results suggested that inclusion of up to 5% PKE (enzyme treated or untreated) in the grower diet did not affect the growth performance of broiler chickens and to avoid any negative effect on the overall, the maximum inclusion rate of PKE is 20% in finisher broiler diet. Dressing percentage and weight of cuts of commercial value (wing, breast meat and thigh-drumstick) as percentage of carcass weight were not significantly different among treatments (P>0.05). Among the internal organs, weight of gizzard in chicken fed PKE diets, particularly in the 30% inclusion level was higher (P<0.05) than the PKE-free control diet. The shear force value, indicating the degree of tenderness of meat for the control was higher (P<0.05) than the corresponding values fed diets supplemented with PKE. In general, color of meat, measured using lightness (L*) and redness (a*) values did not differ between the control and treatment groups (P>0.05) except the yellowness (b*) value of meat in birds fed 30% PKE inclusion rate treatment was higher than those in the control and 20% PKE diets. The intestinal villus height and crypt depth (duodenum, jejunum and ileum) were not different (P>0.05) among treatments except for duodenum crypt depth. However, the villus height and crypt depth of birds in enzyme treated PKE diets were higher (P<0.05) than those in the raw PKE groups. Viscosity of the intestinal digesta was not different (P>0.05) among treatments. Apparent digestibility of dry matter (DM), organic matter (OM) and energy of chickens in the PKE-free control diet were significantly higher (P<0.05) than all treatment groups with PKE, irrespective of inclusion level and enzyme treatment except for apparent digestibility of crude protein and crude fiber. Results of this thesis suggest that exogenous enzyme (consisted mainly cellulase and mannanase) is effective in hydrolyzing the fiber (hemicellulose and cellulose) component and improved the ME values of PKE. However, the positive effects were not reflected in the growth performance in broiler chickens fed the enzyme treated PKE compared to those raw PKE. The results suggest that PKE can be included up to 5% in the grower diet and 20% in the finisher diet without any significant negative effect on FCR in broiler chickens.